Project Based Learning Business Communication Teaching Materials To Improve Vocational School Students' Work Readiness - Winatha, I Komang; Rusman, Tedi; Suroto, Suroto; Turnip, Samuel; Wijoyo, Hadi; Rahmanto, Andi Adam (FKIP Universitas Lampung, 2024)
This research aims to develop business-based communication teaching materials Project Based Learning (PjBL) which is valid and tests its effectiveness in increasing the work readiness of Vocational High School (VHS) students. This research uses the ADDIE development model which includes stages Analysis, Design, Development, Implementation, and Evaluation. The development of teaching materials is carried out based on analysis of student and industry needs, as well as validation by material experts, learning media and practitioners. The research results show that the teaching materials developed are valid and effective in improving students' business communication skills. The test results show a significant increase in pretest and posttest scores, which indicates that students are better prepared to face the world of work after using this teaching material. Apart from that, this research also found that the integration of technology in PjBL learning and collaborative learning can help students develop soft skills that are important for success in the world of work. Based on the research results, it is hoped that this teaching material can be implemented more widely in vocational schools to improve the quality of vocational education in Indonesia.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.224-229